Rick Steves' Florence & Tuscany 2007 - Steves, Rick ; Openshaw, Gene (Emeryville Avalon Travel, 2006)
A guide to the author's favorite destinations in Florence, including the Duomo, the Uffizi, the Bargello, and the Ponte Vecchio.
Keywords: Florence (Italy) -- Guidebooks. Tuscany (Italy) -- Guidebooks. Italy -- Florence. Italy -- Tuscany